The Narrative Impression Is A New Type From Narrative Types - G. Alatwany, Qaiss Sabeeh (Opción, 2019)
The idea of the story impression that I give to the recipient carries purely psy- chological and human dimensions. This scene then raises the implications of the writer’s psychological insides to be expressed on the surface of the paper, and the reader will then enjoy reading the psychological insides of the writer, which may constitute an unusual milestone, and the impression of anecdotal term I proposed to name this type of narrative, which set the limitations sum- marized Balati B Count the examples of the story impression: 1-Anecdotal impression is based on the existence of a particular event earlier than the mo- ment of receipt (the author of the story impression) This event is not imagined, but carries the spontaneous nature of accidental accidentally without prior planning, but carries a factor of influence that attracts this recipient writer and affect it. 2 - space space is often over the presence of time in the embodi- ment of stories, which is a natural result of the reduction mechanism used by the author this mechanism tends to determine the place, and then comes the time (if needed) to complete the meaning, and may not come to the lack of it. 3 - Characters in the story impression open to the embodiment in the biblical fabric in the sense that the number of these characters is logically open as long as the event needs and accommodates them to form elements of the impression to the completion of the meaning and vision story. 4 - Fiction impression of a living embodiment of the writer himself to the end of the impression, which provides the reader the author’s intellectual and political orientations and be- liefs social and religious.